Differentiation between palatal rugae patterns of twins by means of the Briñón method and an improved technique - Lara Maria HERRERA; Raíssa Ananda Paim STRAPASSON; Luiz Eugênio Nigro MAZZILLI; Rodolfo Francisco Haltenhoff MELANI (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract Palatal rugae patterns are anatomic structures considered unique to each person. Monozygotic twins present similarities, however, Rugoscopy in particular, may contribute to their individualization for forensic purposes. The aims of this study were: to study the palatal rugae classifications of Briñón; to propose improvements to facilitate use of this method, if pertinent; and to characterize palatal rugae in a sample of Brazilian monozygotic twins and singletons. Precise reproducibility of the two methods of Briñón, from 1982 and 2011, was prevented by poor intra-examiner agreement (70% and 13% respectively). Our proposed improvements to these methods, although preliminary, were associated with better results. The most common palatal rugae patterns were types A, M, and Q. Palatal rugae were confirmed to be unique to each individual, even in monozygotic twins. Furthermore, twins did not exhibit any special patterns that might facilitate their differentiation from singletons.